Prevalence and antimicrobial susceptibility of Vibrio parahaemolyticus isolated from retail shellfish in Shanghai. (February 2016) - Yu, Qianqian; Niu, Mengya; Yu, Mengquan; Liu, Yanhong; Wang, Dapeng; Shi, Xianming
Abstract: Vibrio parahaemolyticus is a marine and estuarine bacterium that poses the greatest threat to human health worldwide. It has been the leading bacterial cause of seafood-borne illness. This study investigated the prevalence and drug resistance of V. parahaemolyticus isolated from retail shellfish in Shanghai. A total of 140 shellfish samples were collected from February 2014 to February 2015. The occurrence of V. parahaemolyticus in shellfish was 34.3%, which has increased compared to previous reports. In addition, discernible differences of total presumptive V. parahaemolyticus counts (TPVPC) were also observed in shellfish between market A and B. The results from PCR assays indicated that thermostable direct hemolysin ( tdh ) gene was positive in two isolates (2.1%), and the thermostable direct hemolysin-related hemolysin ( trh ) gene was not detected in all isolates. Antibiotic resistance profiles of those isolates were as follows: ampicillin (87.5%), cephazolin (31.3%), cephalothin (6.3%), amoxicillin/clavulanic acid (6.3%), piperacillin (6.3%), and amikacin (3.2%). Thirty-three out of 96 isolates were resistant to two or more antimicrobial agents. It is suggested that V. parahaemolyticus in retail shellfish could be a potential risk to consumers in Shanghai. Highlights: Vibrio parahaemolyticus was found in 34.3% of the shellfish analyzed. Two tdh positive V. parahaemolyticus strains were detected in the summer samples. The V. parahaemolyticus strains have different MAR indices from 0.11 to 0.22. The first generation cephalosporins may be misused widely in the environment. The gills of shellfish could be a good candidate for V. parahaemoluticus detection.